ADIPONECTIN A PLEIOTROPIC BIOMARKER IN MULTISYSTEM PATHOLOGIES & INFLUENCE OF AYURVEDIC HERBS: A SCIENTIFIC APPRAISAL - Narasimha Raju, K. V.; Godatwar, Pawan Kumar (International Journal of Ayurveda and Pharma Research, 2015)
The understanding of metabolic pathologies is made easy with the emergence of the most luring cytokine - Adiponectin, which is produced exclusively by adipocytes and which enhances insulin sensitivity and inhibits many steps in the inflammatory process by exerting its action through its receptors AdipoR1, AdipoR2, and T-cadherin. AdipoR1 is expressed abundantly in muscle, whereas AdipoR2 is predominantly expressed in the liver. In liver, Adiponectin inhibits the expression of gluconeogenic enzymes and the rate of glucose production. In muscle, Adiponectin increases glucose transport and enhances fatty acid oxidation, partially due to activation of AMP kinase. These above physiological activities and many more are performed with the normal or high levels of Adiponectin in the blood whereas the decreased levels of the same leads to various metabolic disorders. The present article encompasses various researches and recent progress made in understanding the biological effects of Adiponectin. These studies confer Adiponectins role as biomarker and mediator in multiple systemic pathophysiologies, thereby establishing its clinical and therapeutic value in the conditions ranging from metabolic syndrome to malignancies. Also presented in this paper is the contribution of Ayurveda in the form of single herbal drugs which show the therapeutic modulation on Adiponectin.